2020
DOI: 10.1002/hbm.25269
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning of tone patterns changes the effective connectivity between Heschl's gyrus and planum temporale

Abstract: Learning of complex auditory sequences such as music can be thought of as optimizing an internal model of regularities through unpredicted events (or “prediction errors”). We used dynamic causal modeling (DCM) and parametric empirical Bayes on functional magnetic resonance imaging (fMRI) data to identify modulation of effective brain connectivity that takes place during perceptual learning of complex tone patterns. Our approach differs from previous studies in two aspects. First, we used a complex oddball para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 71 publications
2
5
2
Order By: Relevance
“…That we found a reduction in top-down inhibition from secondary to primary auditory areas and a lack of modulation of forward connections contrasts with most previous studies in which both forward and backward connections show oddball-related effects (Auksztulewicz & Friston, 2015; Chennu et al, 2016; Garrido et al, 2007, 2008; Garrido, Kilner, Kiebel, et al, 2009; Lumaca et al, 2020; Schmidt et al, 2013). From a predictive coding perspective (Friston, 2005; Garrido, Kilner, Stephan, et al, 2009; Huang & Rao, 2011), forward and backward communication between brain areas reflects the update of predictive models by prediction error.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…That we found a reduction in top-down inhibition from secondary to primary auditory areas and a lack of modulation of forward connections contrasts with most previous studies in which both forward and backward connections show oddball-related effects (Auksztulewicz & Friston, 2015; Chennu et al, 2016; Garrido et al, 2007, 2008; Garrido, Kilner, Kiebel, et al, 2009; Lumaca et al, 2020; Schmidt et al, 2013). From a predictive coding perspective (Friston, 2005; Garrido, Kilner, Stephan, et al, 2009; Huang & Rao, 2011), forward and backward communication between brain areas reflects the update of predictive models by prediction error.…”
Section: Discussioncontrasting
confidence: 99%
“…Another finding that differs from previous research is the lack of involvement of frontal areas in the generation of the MMN, as indicated by the low probability of the opercular family. This is consistent with the lack of frontal generators previously reported for the same dataset (Quiroga-Martinez et al, 2019a) and in a recent fMRI study using simple musical stimuli (Lumaca et al, 2020). This suggests that the opercular peak found in the present source-level statistical analyses may reflect source leakage.…”
Section: Discussionsupporting
confidence: 93%
“…That we found a reduction in top-down inhibition from secondary to primary auditory areas and a lack of modulation of forward connections contrasts with most previous studies in which both forward and backward connections show oddball-related effects (Auksztulewicz & Friston, 2015;Chennu et al, 2016;Garrido, Kilner, Kiebel, & Friston, 2007;Garrido et al, 2008;Garrido, Kilner, Kiebel, et al, 2009;Lumaca, Dietz, Hansen, Quiroga-Martinez, & Vuust, 2020;Schmidt et al, 2013). From a predictive coding perspective (Friston, 2005;Garrido, Kilner, Stephan, et al, 2009;Huang & Rao, 2011) and elicit little model updating (i.e., learning) at higher stages where melodic expectations are likely processed.…”
Section: Connectivity Patterns Underlying the Mmncontrasting
confidence: 99%
“…Another finding that differs from previous research is the lack of involvement of frontal areas in the generation of the MMN, as indicated by the low probability of the opercular family. This is consistent with the lack of frontal generators previously reported for the same dataset (Quiroga-Martinez et al, 2019b) and in a recent fMRI study using simple musical stimuli (Lumaca et al, 2020). This suggests that the opercular peak found in the present source-level statistical analyses may reflect source leakage.…”
Section: Connectivity Patterns Underlying the Mmnsupporting
confidence: 93%
“…Rare but robust empirical supports for predictive coding at play during oddball processing have been reported this past decade, obtained at the psychological level with trial-by-trial computational modelling (Lieder et al, 2013; Ostwald et al, 2012; Stefanics et al, 2018; Weber et al, 2020) and at the physiological level with DCM (Chennu et al, 2016; Fogelson et al, 2014; Garrido et al, 2009; Lumaca et al, 2021; Moran et al, 2013). Novel evidence at the both levels of analysis is provided here in the controlled work using exactly the same brain data informed by simultaneous EEG and MEG.…”
Section: Discussionmentioning
confidence: 91%